Nimrud and Its Remains. Vol. I - Mallowan, M. E. L. (1966)
Preface. Foreword: Ninevite Prelude. I. Nimrud Landscape; II. Progress of the Excavations: The Governor’s Palace; III. We Build a House; IV. Discovery of a Stela; V. The City and Town of Assur-Nasir-Pal; VI. The Ninurta Temple and the Ziggurrat; VII. The N.W. Palace of Assur-Nasir-Pal: Construction and Decoration; VIII. The N.W. Palace of Assur-Nasir-Pal: Discoveries in the Domestic Wing; IX. Treasure-Trove in Well NN of the N.W. Palace; X. Wells in Court AJ and Room AB of the N.W. Palace: Writing on Wax; XI. The N.W. Palace: Northern Wing and Chancery; XII. Private Houses; XIII. The Burnt Palace; XIV. Ezida and the Nabu Temple; XV. The Akropolis Palace (AB): Decline and Fall of Calah; In a separate folder: Folding maps, plans and sections I-VIII.